Experimental and Computational Study of the Antioxidative Potential of Novel Nitro and Amino Substituted Benzimidazole/Benzothiazole-2-Carboxamides with Antiproliferative Activity - Maja Cindrić; Irena Sović; Marija Mioč; Lucija Hok; Ida Boček; Petra Roškarić; Kristina Butković; Irena Martin-Kleiner; Kristina Starčević; Robert Vianello; Marijeta Kralj; Marijana Hranjec (MDPI AG, 2019)
We present the synthesis of a range of benzimidazole/benzothiazole-2-carboxamides with a variable number of methoxy and hydroxy groups, substituted with nitro, amino, or amino protonated moieties, which were evaluated for their antiproliferative activity in vitro and the antioxidant capacity. Antiproliferative features were tested on three human cancer cells, while the antioxidative activity was measured using 1,1-diphenyl-picrylhydrazyl (DPPH) free radical scavenging and ferric reducing antioxidant power (FRAP) assays. Trimethoxy substituted benzimidazole-2-carboxamide 8 showed the most promising antiproliferative activity (IC50 = 0.6−2.0 µM), while trihydroxy substituted benzothiazole-2-carboxamide 29 was identified as the most promising antioxidant, being significantly more potent than the reference butylated hydroxytoluene BHT in both assays. Moreover, the latter also displays antioxidative activity in tumor cells. The measured antioxidative capacities were rationalized through density functional theory (DFT) calculations, showing that 29 owes its activity to the formation of two [O•∙∙∙H−O] hydrogen bonds in the formed radical. Systems 8 and 29 were both chosen as lead compounds for further optimization of the benzazole-2-carboxamide scaffold in order to develop more efficient antioxidants and/or systems with the antiproliferative activity.